Identification of fibril-like tertiary contacts in soluble monomeric α-synuclein - Esteban Martin, Santiago (2013)
Structural conversion of the presynaptic, intrinsically disordered protein α-synuclein into amyloid fibrils underlies neurotoxicity in Parkinson's disease. The detailed mechanism by which this conversion occurs is largely unknown. Here, we identify a discrete pattern of transient tertiary interactions in monomeric α-synuclein involving amino acid residues that are, in the fibrillar state, part of β-strands. Importantly, this pattern of pairwise interactions does not correspond to that found in the amyloid state. A redistribution of this network of fibril-like contacts must precede aggregation into the amyloid structure.